Constitutional restrictions and guarantees governing the dissolution of the House of Representatives in the Jordanian constitutional system of 1952 - Al Maagbeh, Moh'd Mofadi Faleh; Allaymoon, Awad Rajab; Altarawneh, Shadi Meeush D’yab; Alhendi, Noor; Al Maaqbeh, Abdullah Mohammad Mofadi; Altaani, Muhanned Farhan Mohammad; Almadi, Mesh’al Daher (Research Journal in Advanced Humanities, 2026)
This study deals with the provisions of the previous and subsequent constitutional restrictions and guarantees governing the dissolution of the House of Representatives in accordance with the Jordanian constitution 1952. These restrictions and guarantees is a constitutional obligation and the competent authority shall comply with since these restrictions and guarantees consider as one of the tools of balance between the authorities of the state and its nonexistence may result in the absence of parliament as one the pillars of the Jordanian constitutional system of representatives.The most important of these guarantees is the issuance and reasoning of the royal decree by the king. This study is also explained the subsequent restrictions results from dissolution of the House of Representatives such as: the necessity of holding and election for the House of Representative within four months from the date of dissolution. The constitutional amendment also requires that the government shall submit its resignation within one week from the date of dissolution. Furthermore, this study explained the consequences of the failure to comply with these restrictions and some of these consequences are explained by the legislator as a penalty the failure to comply with these guarantees and restrictions.This study concluded with a number of particular results. The most important of which is the significance of the constitutional amendment of 2011 which provides that the government –in the tenure of which the House of Representatives is dissolved- shall resign and the failure of the competent authority of dissolution to comply with the reasoning of dissolution